Effectiveness of galcanezumab on sleep quality, migraine outcome, and multidimensional patient-reported outcome measures: a real-world experience in Turkish patients with episodic and chronic migraine - Ilgaz Aydinlar, Elif; Erdogan Soyukibar, Tuba; Yalinay Dikmen, Pinar (Frontiers in Neurology, 2024)
Introduction This real-world study aimed to investigate the impact of galcanezumab on sleep quality, migraine outcome and multidimensional patient-reported outcomes measures (PROMs) in patients with episodic migraine (EM) and chronic migraine (CM). Methods Fifty-four patients with episodic migraine (n = 24) or chronic migraine (n = 30) received a 3-month series of galcanezumab injections and were evaluated for sleep quality, measured using the Pittsburgh Sleep Quality Index (PSQI), as well as migraine outcomes such as monthly headache days (MHDs), monthly migraine days (MMDs), and headache severity. Patient-reported outcome measures (PROMs) such as the Migraine Disability Assessment Scale (MIDAS), Headache Impact Test-6 (HIT-6), SF-36 Health-related Quality of Life (HRQoL), Beck Anxiety Inventory (BAI), and Beck Depression Inventory (BDI) were additionally included in the assessment. Results The percentage of patients with poor sleep quality (total PSQI scores ≥ 5) was 72.7% at baseline, decreasing to 57.5% and 56.2% at the 1st and 2nd months, respectively. By the 3rd month of galcanezumab injections, significant improvement was observed in the sleep disturbances domain in the overall study population (p = 0.016), and in subgroups of patients with low anxiety levels (p = 0.016) and none/minimal depression (p = 0.035) at baseline. Patients with sleep disorder at baseline exhibited marked improvements in total PSQI scores (p = 0.027) and in the subjective sleep quality (p = 0.034) and daytime dysfunction (p = 0.013) domains, by the 3rd month. Over the 1st, 2nd, and 3rd months, there were significant improvements in MHDs (p < 0.001), MMDs (p < 0.001), HIT-6 scores (p < 0.001 for each), BAI scores (p < 0.001 for each), BDI scores (p ranged from 0.048 to <0.001), and HRQoL scores (p ranged from 0.012 to <0.001). Conclusion Galcanezumab demonstrates notable benefits in improving sleep quality, along with a comorbidity-based and domain-specific effect on sleep parameters, which involved sleep disturbances domain in patients without depression or anxiety at baseline but the total PSQI scores, subjective sleep quality and daytime dysfunction in those with sleep disorder at baseline. The treatment also facilitates rapid-onset enhancements in migraine outcomes as well as various PROMs.